Complicated appendicitis in a COVID -19 positive child: A case report (Indian Journal of Case Reports, 2021)
Appendicectomy is the standard management for acute appendicitis. The pandemic has made us aware of the risks of surgical procedures associated with coronavirus disease 2019 (COVID-19) infection. Here, we present the case of a 5-year-old COVID-positive male child who came with high-grade fever and pain in the abdomen along with vomiting. He was diagnosed to have appendicular perforation with an abscess on abdominal ultrasonography and computerized tomography scan. In view of COVIDs positive status and continued clinical and radiological improvement with intravenous (IV) antibiotics, he was managed conservatively. There was complete resolution of the abscess on follow-up, thereby deferring the need for surgery and thus avoiding complications associated with the procedure. Recent evidence suggests that conservative management with IV antibiotics in selected patients may provide a favorable outcome. This will reduce the morbidity and mortality associated with surgery of a COVID patient. Our case report supports the role of a conservative approach in the management of acute complicated appendicitis in a COVID-positive child.